Geomorphology and Geology Studies Using Digital Elevation Model (DEM) Data In the Watershed Area of Kampar Regency, Riau Province - Husnul Kausarian; Sandy Masdriyanto; Batara; Adi Suryadi; Muhammad Zainuddin Lubis (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
This research was conducted in the area of ​​Kampar Regency, Riau Province .it was located at coordinates including 01° 00' 40" - 00° 27' 00" South Latitude and 100° 28' 30"- 101° 14' 30" East Longitude. The purpose of this study was to determine the geological condition of the watershed, and it was determined the geomorphological condition of the watershed, to determine the number of divisions of the watershed, to determine the relationship between the watershed and rainfall, to determine the geological and geomorphological relationship with the watershed in the study area. The method used starts from field sampling, core description, distribution analysis of geological data, geomorphology, watershed analysis, and analysis of rainfall. Based on the analysis of the distribution of geological data in the research area, there were 12 geological formations from the results of geological mapping, namely: the Sihapas Formation, the Telisa Formation, the bekasap formation, the Bahorok Formation, the Farmer Formation, the Manggala formation, the Talang Akar formation, the Telisa Atas formation, the Palembang Tengah formation, Basement, members of the Lower Palembang formation (Air Berakat), members of the Upper Palembang formation (Muara Enim). In subsurface geology there were 8 well points in the study area, 2 correlations were carried out, namely the 1st correlation between CR-04, CR-03, CR-01, CR-02, CR-08, and the 2nd correlation between CR-05, CR-06, CR- 07. Geomorphological conditions were divided into 4 namely lowland areas, low hill areas, hilly areas, and high hill areas. The watersheds in the research area were divided into 2 watersheds, namely the Kampar and Siak watersheds. Watershed rainfall observations in the study area for 5 years from 2015 – 2019 were located at 5 different stations, with fluctuating rainfall intensity